The Role of Structural Funds in Developing Learning Regions - Jari Ritsilä; Jukka Haukka (European Regional Science Association (ERSA), 2003)
The thematic background of learning regions is based on the concept of learning organisations and on the paradigm of the innovative milieu. The frame of reference of the learning regions can be seen as a synthesis of regional and organisational based definitions, which involve the process of learning. Compared to the theory of learning organisations, the most challenging question is to find the collective mission among a heterogeneous group of actors, which involves individuals, organisations, enterprises etc. The key processes of learning regions can be divided in the three categories. The first element in the concept of learning regions is producing and enhancing human capital in individual, organisational and regional level. The formation of new human capital plays an important role in innovation process and it is also closely linked to learning process, which can be realized through new technological and scientific innovations. The second element is the cooperation of regional actors and the diffusion of human capital and know-how in and between the organisations. This can be seen as an opportunity to gain agglomeration benefits. The third - and perhaps the most important - issue in the framework of learning regions is how human capital and new know-how can be transferred to practise. From regional point of view this means growing GDP, employment, better quality of services and welfare. The basic pillars of the European social fund are based on education, employment and know-how. Presumably, structural fund based acts on regional level have a catalytic influence on the key processes of learning regions. The basic processes which can be affected by ESF are the producing new human capital, subdividing the know-how and transferring it to practice. It is also clear that sustainable regional competitiveness needs social inclusion as a basement. The social inclusion is important part of ESF acts, and in that way the projects funded by ESF are also closely related to the concept of learning regions. In this paper, we explore what is the role of ESF interventions in developing regional competitiveness. The study is based on the concept of learning regions, and it is based on dissection of register based sample of ESF-projects, which covers over 30% of projects of ongoing ESF period 2000-2006 in Finland. Main purpose of this paper is to find out, how projects are integrated to the processes of learning region (enhancing human capital, the diffusion of human capital and transferring it to practise).
Keywords: 330